Trade in services: examples for SADC - Lehloenya, P. M. (Faculty of Law, University of the Free State, 2003)
English: Over the last few decades, the services sector has become an important component of world trade and the main income earner for many countries. Accelerated by the process of liberalisation, the effects of trade in services now traverse all countries. The main participants and beneficiaries, however, remain developed countries, while developing countries continue to play a marginal role. This comes as a result of a variety of factors ranging from developing countries' inexperience in producing services for export purposes, to trade rules that are more favourable to developed countries, to the complexity and cost of the measures necessary for developing countries to make a successful transition to the new arrangements under liberalisation. Notwithstanding the adverse conditions, opportunities exist in the legal framework developed under the WTO for developing countries to participate more meaningfully in trade in service. These include, inter alia, the possibility of collaborating with foreign firms and benefiting from their experience, as well as establishing regional joint ventures that can compete more effectively at the international level. In the end, the success of developing countries in penetrating the international services market will be determined by the extent to which their domestic service providers manage to adapt to the new trade environment, how all these countries exercise their options in choosing which services to liberalize and their timing in doing so, as well as their ability to resist pressure from developed countries to act against their better judgement.

Afrikaans: Oor die afgelope paar dekades het die dienste sektor 'n belangrike komponent van wêreldhandel geword en is dit die hoof/vernaamste inkomste verdiener vir baie lande. Verhaas deur die proses van liberalisering, oorkruis die uitwerkings van handel in dienste nou alle lande. Die hoof deelnemers en bevoordeeldes bly egter ontwikkelde lande, terwyl ontwikkelende lande aanhou om 'n mindere rol te speel. Dit is as gevolg van 'n verskeidenheid faktore wat strek van ontwikkelende lande se onervarenheid om dienste vir uitvoerdoeleindes te produseer, na handelsreëls wat meer gunstig is vir ontwikkelde lande, na die ingewikkeldheid en die koste van die afmetings wat noodsaaklik is vir ontwikkelende lande om 'n suksesvolle oorgang te maak na die nuwe reëlings onder liberalisering. Nieteenstaande die ongunstige toestande, bestaan daar geleenthede in die regsraamwerk ontwikkel onder die WHO vir ontwikkelende lande om meer sinvol deel te neem in handel in dienste. Dit sluit in, inter alia, die moontlikheid om saam te werk met buitelandse firmas en te baat van hulle ervaring, sowel as die stigting van streeks gesamentlike ondernemings wat meer effektief op internasionale vlak kan kompeteer. Aan die einde sal die sukses van ontwikkelende lande om deur te dring in die internasionale dienstemark bepaal word deur die bestek/omvang waartoe hul binnelandse diensverskaffers daarin slaag om aan te pas tot die nuwe handelsomgewing, hoe al hierdie lande hul opsies uitoefen om te kies watter dienste om te liberaliseer en hul tydsberekening om dit te doen, sowel as hul vermoë om druk van ontwikkelde lande om teen hul beter oordeel op te tree te weerstaan.